THE PHENOMENON OF INDEPENDENCE IN CHILDREN AND ITS CONFORMITY TO BE EXPLAINED THROUGH - Abdullaeva Nigora Rahimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article demonstrates the identification of the Conformity phenomenon in adolescent swimmers in children through several methods of distinguishing it from some similar phenomena.